Experimental alternative to investigate the radiation-induced radical chemistry at the molecular level. Issue 15 (January 2020) - Beydoun, A; Lecomte, F; Nieuwjaer, N; Desfrançois, C; Manil, B
Synopsis: This project aims to develop an original approach to investigate the damage at the molecular level on biomolecules from the indirect irradiation effects. We will construct a new device to put biomolecules in the gas phase, based on the soft laser desorption from microdroplets directly into vacuum, and this source will be coupled with an irradiation platform.